Comparison of Design Flood Hydrograph Using XP-SWMM in Jeluh River, Kajang for Flood Mitigation - Mohd Sidek L.; Zaki A.Z.I.A.; Puad A.H.M.; Mustaffa Z. (Springer, 2023)
There are several flood event recorded within the Kajang Town in recent years especially in 2008, 2011 and 2012. Intense development of housing and commercial activities mainly concentrated within Kajang town in these recent years adjoined with its flood plain location contributed to Kajang town and its surrounding areas being prone to flooding issues. Therefore, the hydrological analysis is required to obtain the design flood hydrograph based on the different hydrological method. In this research XP-SWMM software-based hydrological modeling is done for Jeluk River, Kajang. The results show how a different method of hydrological analysis can be affected by the different types of input parameters and give a dissimilar set of flood hydrographs. This analysis also shows that the different method of hydrological analysis can give the best design flood hydrograph based on the best available data information and suit the rainfall pattern of a country. 2020, Springer Nature Singapore Pte Ltd.